An Investigation of Factors Influencing Intention to Use Mobile Wallets of Mobile Financial Services Providers in Myanmar - Min Tun, Phyo (School of Business and Management Institut Teknologi Bandung, 2020)
Abstract. Mobile wallet is becoming an innovative financial product in the globe and is well expanding quickly into developing countries. This empirical study proposes a comprehensive research model in an amalgamated way consisting of beliefs, social, quality, and trust aspects, to fill up the gaps of previous research studies in similar contexts. The quantitative research is employed to investigate six factors with behavioral intention to use a mobile wallet. Structural Equation Modeling (SEM) technique was applied to analyze data and formulate the results. Survey data were collected from 234 potential mobile wallet users in Myanmar. The results of the study indicated that trust and perceived usefulness factors are significantly influencing behavior intention to use a mobile wallet in Myanmar. But service quality, user satisfaction, facilitating conditions, and social influence are statistically insignificant. The result of this study can be utilized by user acquisition managers, marketing managers, and business development managers to formulate the strategies and approaches for positioning their mobile wallet among a suitable user base, thereby acquiring more mobile wallet users.Keywords: Mobile wallet, mobile financial service, financial technology, behavioral intention